Clinical Outcomes and Complication Rates of Endodontically Treated Teeth with Fixed Dental Prostheses: A Retrospective Study - Sarah Aloqayli; Hanin Alsalhi; Ali Alenezi (Dentistry Journal)
Background/Objectives: Endodontically treated teeth (ETT) often have significant structural damage and require multiple reinforcing methods during the reconstruction process. The aim of this study was to evaluate the complication rates of ETT with and without a post. Methods: The study investigated various clinical factors, including technical complications as well as biological complications. All patients who had previously received fixed dental prostheses (FDPs) were subjected to clinical and radiographical examinations during their follow-up visits. Clinical and radiographic assessments were performed to determine the cumulative survival rate, and life table survival analyses of FDPs in the presence of complications were performed. Results: A total of 287 ETT were evaluated in this study, in which 219 were placed in females and 68 in males, with an average follow-up time of 82.4 months. There were no significant differences between ETT with a post and ETT without a post regarding the complication rates. The complication rates of the FDPs without a post revealed a survival rate of 58% after 5 years, 44% after 10 years, and 29% after 15 years. On the other hand, the complication rates of the FDPs with a post revealed survival rates of 50%, 30%, and 21% after 5, 10, and 15 years, respectively. The Kaplan–Meier survival analysis showed no significant differences in the complication rates, regardless of the existing of the posts (p = 0.830). Conclusions: ETT restored with FDPs with or without a post can show similar complication rates in a long-term evaluation. Furthermore, the types of final restoration may not have an effect on the complication rate with ETT.